KAHOOT APPLICATION: ANDROID BASED WORKSHEET MEDIA DEVELOPMENT IN FOSTERING GRAMMAR UNDERSTANDING - Vina Rosyadah; Anita Rahmah Dewi; Wilujeng Asih Purwani; M. Labib Al Halim (E-LINK JOURNAL, 2022)
This study aims to develop the Android-based worksheet media by Kahoot application on grammar and analyze the feasibility of it. This design of this study uses Research & Development (R&D) method which uses ADDIE model by Dick & Carey (1996). Data collection techniques were carried out through interviews, questionnaires by validity tests data and data feasibility tests, and documentation. The validation of learning media was carried out by media and material experts, and English teachers. The media was tested on 18 students of X MIPA. Data analysis techniques use mixed method by percentages. The results of this study indicate that the media is feasible to use because it has been approved by experts with 96% media percentage, 78% material, 92% teacher and 83.8% student response percentage. In addition, media is more fun and students can encourage their curiosity also foster them in understanding grammar. Keywords: Android, Development, Grammar, Kahoot Application, Worksheet Media